PERAN GURU DALAM PENGUATAN PENYELENGARAAN SEKOLAH RAMAH ANAK - Fauzan, Rizki; Mustaidah; Soejono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the role of teachers in strengthening the implementation of Child-Friendly Schools (CFS) at SMA Negeri 1 Moga based on the Among System by Ki Hadjar Dewantara. The research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that teachers play a crucial role in implementing the principles of